Efficacy and safety of endoscopic radiofrequency ablation for unresectable extrahepatic cholangiocarcinoma: a randomized trial - Yang, Jianfeng; Wang, Jing; Zhou, Haibin; Zhou, Yifeng; Wang, Yang; Jin, Hangbin; Lou, Qifeng; Zhang, Xiaofeng (Endoscopy, 2018)
Background Endoscopic placement of biliary stents to relieve jaundice is the main palliative treatment for unresectable extrahepatic cholangiocarcinoma. Endoscopic biliary radiofrequency ablation (RFA) has been reported to prolong stent patency, which may be beneficial in improving patient survival. However, available evidence is still insufficient, as most reported studies are retrospective case series. The aim of this study was to explore the clinical effect and safety of RFA in patients with unresectable extrahepatic cholangiocarcinoma. Methods 65 patients with unresectable extrahepatic cholangiocarcinoma, except Bismuth type III and IV hilar cholangiocarcinoma, were enrolled and randomly underwent either RFA combined with biliary stenting (RFA + stent group; n = 32) or biliary stent only (stent-only group; n = 33). Overall survival time, stent patency period, and postoperative adverse events were recorded.Results In the 21-month follow-up period, the overall mean survival time was significantly longer in the RFA + stent group than in the stent-only group (13.2 ± 0.6 vs. 8.3 ± 0.5 months; P < 0.001). The mean stent patency period of the RFA + stent group was also significantly longer than that of the stent-only group (6.8 vs. 3.4 months; P = 0.02). There was no significant difference in the incidence of postoperative adverse events between the two groups (6.3 % [2/32] vs. 9.1 % [3/33]; P = 0.67).Conclusion Endoscopic RFA combined with stenting can significantly prolong survival and the stent patency period without increasing the incidence of adverse events in patients with extrahepatic cholangiocarcinoma patient, except Bismuth type III and IV hilar cholangiocarcinoma. This approach can be considered as a safe and effective palliative treatment for these patients.